2H → 1T phase transition and hydrogen evolution activity of MoS2, MoSe2, WS2 and WSe2 strongly depends on the MX2 composition1. Issue 40 (18th May 2015) - Ambrosi, Adriano; Sofer, Zdeněk; Pumera, Martin
<x xml:space="preserve">Abstract</x> We investigate herein the 2H → 1T phase transition upon chemical exfoliation of the four most widely considered TMD materials: MoS2, MoSe2, WS2 and WSe2.